IMPROVEMENT OF TECHNOLOGY OF SALES ON THE BASIS OF USE OF MECHANISMS OF SEARCH OPTIMIZATION - N. Kazakova; L. Mikhailova; A. Sazonov (Вестник университета)
The technology of search optimization as one of elements of the digital marketing directed to increases in volume of Internet sales at the present stage of development of economy has been analyzed. The details of the process of drawing up an algorithm of search optimization of the website including necessary actions for carrying out internal and external optimization have been presented. The comparison of different types of optimization has been proved. In the conclusion process of work with information necessary for improvement of content of the website and optimization of sales propositions has been considered.